The London Missionary Society and the Problem of Authority in India, 1798-1833 - Kitzan, Laurence (Church history, 1971)
To begin missionary activity in India was not a simple matter. The missionaries there had to face a great deal of opposition not encountered by the missionaries to the South Seas and Africa. In the latter areas the really serious difficulties did not arise until the mission fields had actually been entered. In the case of the Indian missions the missionaries found the first line of osbtruction in England itself, in the London offices of the East India Company. The Company was resolutely opposed to the introduction of missionaries into its own territories, or into any part of India.